Merek Terkenal Menurut TRIPS Agreement dan Penerapan dalam Sistem Merek Indonesia - Insan Budi Maulana (Jurnal Hukum IUS QUIA IUSTUM, 2000)
The matter of legal protection to the well-known trademark holder isnot only viewed from its legal aspects, but also from another facet, such as social and economy aspects In the society. These views should also be applied to the protection of the trademark in Indonesia. How is the reai well-own trademark protection based on the TRIPS Agreements? And what is the relationship of application to the trademark system in Indonesia? This article will discuss these questions.